PERAN WANITA PENGRAJIN GERABAH DALAM MENUNJANG EKONOMI KELUARGA DI DESA MASBAGIK TIMUR KECAMATAN MASBAGIK KABUPATEN LOMBOK TIMUR - Ilyani Indria Lestari; Hety Mustika Ani (Economic Education, University of Jember, 2016)
This study aims to descrypt the public role and eceonomic contribution of women pottery artisans in supporting families economic in the village of Masbagik Timur Masbagik district Lombok Timur regency. This study in a qualitative research with descriptive approach. Data collection methodes used in this research is depth interviews, observations and documens. This reseacrh conducted to 5 women pottery artisans residing in Penakak hamlet dan has husbands with low incomes. The result showed their public role done with economic activities and social activities. Economic activitiy in an effort to support the family economic is done by making pottery that has been occupied for 5-25 years, the allocated time is 6-7 hours each day, andit took two weeks to get results. The social activities that they are doing are social gathering activities, teaching activities and activities of mutual cooperation. Economic contribution given by them to the family income ranges from 21% - 40 % with an average contribution of 28.26%. their economic contribution is used to support the family economy that cannot be fulfilled by the husband’s income that is only able to fulfill their food needs.